2018
DOI: 10.3390/nu10111803
|View full text |Cite
|
Sign up to set email alerts
|

Fruit and Vegetable Consumption and Their Polyphenol Content Are Inversely Associated with Sleep Duration: Prospective Associations from the UK Women’s Cohort Study

Abstract: This study aims to investigate the prospective associations between fruit and vegetable (FV) intakes and their polyphenol content with subsequent sleep duration in UK women. In this study, 13,958 women with ~4 years of follow-up in the UK Women’s Cohort Study were included in the analyses. FV intakes were assessed at baseline using a food frequency questionnaire (FFQ), and average hours of sleep per day were self-reported in follow-up. Polyphenol intake was calculated by matching FV items from the FFQ with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 51 publications
4
21
0
Order By: Relevance
“…There was a persistent inverse association between isoflavone intake and sleep duration suggesting these effects are due to the estrogenic contents of isoflavones [242]. These inverse associations were consistent with our study exploring the prospective associations between polyphenols derived from FV and sleep duration in UK women [83]. To our knowledge, our study is the first prospective study to explore associations between FV items and their polyphenol content with sleep duration.…”
Section: Mechanisms For the Relationship Between Sleep And Fruit Asupporting
confidence: 87%
See 1 more Smart Citation
“…There was a persistent inverse association between isoflavone intake and sleep duration suggesting these effects are due to the estrogenic contents of isoflavones [242]. These inverse associations were consistent with our study exploring the prospective associations between polyphenols derived from FV and sleep duration in UK women [83]. To our knowledge, our study is the first prospective study to explore associations between FV items and their polyphenol content with sleep duration.…”
Section: Mechanisms For the Relationship Between Sleep And Fruit Asupporting
confidence: 87%
“…Most of the studies were conducted in US populations and only two observational studies had their primary objective to assess the association between sleep duration and FV consumption in pregnant women [80] and Chinese older adults (≥65 years) [81]. We conducted the other two prospective studies between sleep duration and FV consumption in UK adults [82,83]. Testing for non-linear associations has been recommended between sleep measures and dietary intakes [29], however—apart from our studies [82,84]—no study assessed non-linear associations (Table 1).…”
Section: Sleep and Fruit And Vegetable Consumptionmentioning
confidence: 99%
“…To date, only one recent study has investigated the relationship between dietary (poly)phenols derived from fruit and vegetables and sleep duration [39]. The study was conducted on 13,958 women with about 4 years of follow-up in the UK Women's Cohort Study: total fruit and vegetable consumption and their estimated content of total polyphenols were directly associated with sleep duration, while individual (poly)phenol classes were not associated with the outcome of interest [39]. Despite no other studies being focused on polyphenols, some studies reported a direct relationship between sleep duration and quality, and fruit and vegetable intake [40,41].…”
Section: Discussionmentioning
confidence: 99%
“…There is a suggestion from animal studies that phytochemicals can influence sleep/wake cycles (Noorwali et al . ). However, whether serotonin in the diet improves sleep remains unclear (St‐Onge et al .…”
Section: Why Are People Sleeping Less and How Can We Sleep Better?mentioning
confidence: 97%
“…) and in a recent prospective cohort study, high intakes of fruit/phytochemicals were inversely related to sleep although the effect size was small (Noorwali et al . ). A review investigating the effects of diet on sleep quality concluded that although it remains unknown at this time if specific foods can improve sleep, some evidence suggests that certain dietary patterns which include higher intakes of fruit and vegetable, wholegrains ( i.e .…”
Section: Why Are People Sleeping Less and How Can We Sleep Better?mentioning
confidence: 97%